ROLA REFLEKSJI W PRZYGOTOWANIU UCZNIA DO KOMUNIKACJI MIĘDZYKULTUROWEJ NA LEKCJI JĘZYKA ROSYJSKIEGO - Karolczuk, Marzanna (Neofilolog, 2019)
This article attempts to identify measures for teaching and learning a foreign language with focus on the reflective and conscious approach. The objective is to develop appropriate attitudes on the part of learners towards Russia and Russians and thus to prepare them for intercultural communication during lessons of Russian as a second foreign language in school. During these lessons work on student attitudes requires the teacher to use multi-faceted techniques and forms of teaching. Among these, worth mentioning is the use of reflective visualization, comparison of cultures, and conscious emphasis of what is valuable and interesting in others. Techniques, which appeal to the emotions of students, and develop their empathy are used in the context of Russian as a second foreign language in school.